-4(n-3)=

Simple and best practice solution for -4(n-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(n-3)= equation:


Simplifying
-4(n + -3) = 0

Reorder the terms:
-4(-3 + n) = 0
(-3 * -4 + n * -4) = 0
(12 + -4n) = 0

Solving
12 + -4n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -4n = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -4n = 0 + -12
-4n = 0 + -12

Combine like terms: 0 + -12 = -12
-4n = -12

Divide each side by '-4'.
n = 3

Simplifying
n = 3

See similar equations:

| 7(x+35)=273 | | 13/15+(8/15)= | | 8.28=5r | | -2(6+x)= | | 2(x+12)=3*x-31 | | (10j-7)-(9j+2)= | | 3x+22+5y+11=180 | | 5y+11=180 | | x-2+3=7 | | (63+5)+(72-3)= | | 8+5(x+3)+7x=x | | (7y+1)(3y-4v-2)= | | 2(4x+1)=42 | | 9+3m= | | (7t+5)+(8t-3)= | | 4x^3-3x^2+9=0 | | 4x-8=79+9x | | 2x+2u=5 | | 1/2(6x-10)+1/3(6+9x)= | | 4x^2-19x+23=-4x+9 | | 12v-11v=18 | | 10(2.1q-2)+(7.5q+19)= | | 5x-2x-2x=17 | | 9m+m+3m-12m+3m=12 | | 8g-6g-8=2g | | 12z-11z=8 | | 5x+(3x-2)=-3-(-4x) | | x=(x*0.1)+(x*0.02)+5+100 | | (13x+50)-(80x+120)= | | 8k-7k=5 | | (13x+50)+(80x+120)= | | 17q-14q=6 |

Equations solver categories